Exophiala lecanii-corni keratitis presenting as a serpiginous pigmented superficial lesion: a case report. Issue 36 (4th September 2020) - Miyakubo, Tomoko; Todokoro, Daisuke; Satake, Yoshiyuki; Makimura, Koichi; Miyakubo, Sumiko; Akiyama, Hideo
Abstract: Rationale: Patients with bullous keratopathy (BK) treated by Descemet stripping automated endothelial keratoplasty (DSAEK) have a compromised cornea, due to the administration of topical steroid, postsurgical use of contact lenses, and impaired barrier function of the corneal epithelium by BK. We report a case of Exophiala lecanii-corni ( E lecanii-corni) keratitis presenting as a serpiginous pigmented superficial lesion after DSAEK. Patient concerns: An 81-year-old woman who had undergone cataract surgeries, suffered from decreased vision in the left eye. She was diagnosed BK and she underwent DSAEK. Two months after DSAEK, a pigmented superficial lesion developed on the left cornea. The lesion migrated and recurred repeatedly and she was referred to our department. Best corrected vision was 20/220. Diagnoses: Light microscopy of a corneal scraping revealed branching fungal hyphae. Fungal culture showed growth of a black colony, identified as E lecanii-corni by ribosomal DNA sequencing. Interventions: We started topical treatment with 1% voriconazole and 1.5% levofloxacin. Antifungal susceptibility testing showed that the minimum inhibitory concentration of voriconazole was 0.06 μg/mL. Outcomes: The lesion scarred after treatment for 3 months, and left best corrected vision improved to 20/40. Lessons: Genus Exophiala is known as 1 of the "black molds" and a cause of chromomycosis. This is the first description of E lecanii-corni keratitis, and pigmented corneal epithelial lesions may be characteristic of this fungal genus.